2019
DOI: 10.14414/jebav.v21i3.1233
|View full text |Cite
|
Sign up to set email alerts
|

The impact of managerial ownership, institutional ownership, proportion of independent commissioner, and intellectual capital on financial distress

Abstract: Financial distress is a phase of the decline in the financial condition experienced by a company before the bankruptcy or liquidation occurs. One of the causes of financial distress is the company’s operating losses, caused its operating cash flow to be negative. During 2014-2016, there was 24 percent of manufacturing companies listed in Indonesia Stock Exchange (BEI) that has a negative pretax profit. The purpose of this study was to obtain empirical evidence of the effect of managerial ownership, institution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 0 publications
3
11
1
3
Order By: Relevance
“…The managerial ownership variable has a positive effect and is likely to have a probability of default compared to nondefault, so the greater the composition of directors' ownership in stocks will have the opportunity for the probability of default, as previously stated that there is too little data on company managerial ownership in this study which happens to be found in companies that have probability of default. This result is supported by previous research which concludes that managerial ownership has a positive effect on financial difficulties (Widhiadnyana & Dwi Ratnadi, 2019). The R&D variable has a negative effect and is likely to have a decreased probability of default if there is an increase in R&D investment spending.…”
Section: Figure 2 Roc Curvesupporting
confidence: 81%
“…The managerial ownership variable has a positive effect and is likely to have a probability of default compared to nondefault, so the greater the composition of directors' ownership in stocks will have the opportunity for the probability of default, as previously stated that there is too little data on company managerial ownership in this study which happens to be found in companies that have probability of default. This result is supported by previous research which concludes that managerial ownership has a positive effect on financial difficulties (Widhiadnyana & Dwi Ratnadi, 2019). The R&D variable has a negative effect and is likely to have a decreased probability of default if there is an increase in R&D investment spending.…”
Section: Figure 2 Roc Curvesupporting
confidence: 81%
“…Jika stabilisasi internal baik, maka tingkat terjadinya financial distress dapat dikurangi. Namun demikian, pada perusahaan yang dipegang oleh pribadi juga memiliki potensi positif karena lebih mudahnya konsolidasi antar pemegang saham (Paramastri & Hadiprajitno, 2017) (Widhiadnyana & Dwi Ratnadi, 2019). Oleh karena itu variabel kepemilikan institusional secara langsung tidak berpengaruh signifikan terhadap financial distress.…”
Section: Hipotesis 2 Pengaruh Kepemilikan Intitusional Terhadap Finan...unclassified
“…The results of the research by Widhiadnyana & Dwi Ratnadi [18] stated that intellectual capital has a negative effect on financial distress, which means that if the company's intellectual capital increases, the company will avoid financial distress.…”
Section: ) the Influence Of Intellectual Capital As A Moderating Vari...mentioning
confidence: 99%